Globalization, Social Identity, and Cooperation: An Experimental Analysis of Their Linkages and Effects - Gianluca Grimalda; Nancy Buchan; Marilynn Brewer (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2015)
Globalization is defined as an individual's connectivity in global networks. Social identity is conceptualized as attachment and identification with a group. We use questionnaire items to measure individual involvement with global networks along with local, national, and global social identity. Propensity to cooperate is measured in experiments involving local and global others. Firstly, we analyse possible determinants of global social identity, showing a significant and positive correlation with an index of individual global connectivity. Secondly, we find a significant mediating effect of global social identity between individual global connectivity and propensity to cooperate at the global level. This is consistent with a cosmopolitan hypothesis of how participation in global networks reshapes social identity: increased participation in global networks increases global social identity and this in turn increases propensity to cooperate with others.
urn:nbn:de:hbz:464-20160127-143122-6
Keywords: 320; Globalization; social identity; cooperation; cosmopolitanism